Ocena dostępności zasobów służących realizacji polityki zdrowotnej w szkołach należących do Sieci Szkół Promujących Zdrowie w Polsce - Leksy, Karina; Gawron, Grzegorz (Studia Edukacyjne, 2025)
Health is the fundamental value of human life and the primary determinant of the functioning quality in the individual and collective dimensions. Health is the capital that the state must invest in at various policy levels. It should include the school system, with school health policy focused on effective prevention, education, and health promotion. The Polish Network of Health Promoting Schools (HPS) is trying to compensate for perceived systemic neglect. It is an association of schools attempting to implement a comprehensive approach to health promotion. However, the effectiveness of the activities is determined mainly by the availability of personal, time, and financial resources in schools. This issue was discussed in the 2023 nationwide survey (CAWI) carried out among school health promotion coordinators from the HPS Network. The article presents selected results relating directly to the assessment of the availability of resources for the implementation of school health policy and the declaration of adapting HPS principles to local conditions. Although there are significant differences in the assessment of school resources, the coordinators jointly emphasize their importance for the optimal implementation of school health policy. Therefore, for any school attempting to implement its health policy, it should be a priority to identify and provide resources that reflect the school environment’s specific needs in the health field and its promotion.